Engendering Economics: conversations with women economist in the United States - Olson, Paulette I.; Emami, Zohreh (London ; New York : Routledge, 2002)
This book demonstrates that women's experiences in economics not only differ from those of men, but from those of each other.The result provides a rich picture of the sociology of the economic proffession and the vital contributions made to it by women economists.
Includes bibliographical references (p. 250-257) and index.
aia 09/09/13; rpm 20/09/13
Loans
Keywords: Women economists -- United States -- Biography; Feminist Economics . Economics